2018
DOI: 10.1128/jvi.01444-18
|View full text |Cite
|
Sign up to set email alerts
|

Comparative In Vitro and In Vivo Analysis of H1N1 and H1N2 Variant Influenza Viruses Isolated from Humans between 2011 and 2016

Abstract: Influenza A virus pandemics are rare events caused by novel viruses which have the ability to spread in susceptible human populations. With respect to H1 subtype viruses, swine H1N1 and H1N2 viruses occasionally cross the species barrier to cause human infection. Recently isolated from humans (termed variants), swine viruses were shown to display great genetic and antigenic diversity, hence posing considerable public health risk. Here, we utilized and approaches to provide characterization of H1 subtype varian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 73 publications
5
35
0
Order By: Relevance
“…However, in comparison with ferrets, titers in pigs were lower and, in some contact pigs, were below the positive threshold. These findings are comparable with outcomes reported for pH1N1 virus infection of pigs and ferrets (36,37,39,40) and a comparison of swine H1 viruses, including H1N2v strains, when infecting ferrets (41). A North American reassortant H1N1 swine IAV incorporating pH1N1-origin polymerase acidic, NP, and M genes also reportedly showed similar replication kinetics to a swine IAV pH1N1 isolate when infecting ferrets (14).…”
Section: Discussionsupporting
confidence: 86%
“…However, in comparison with ferrets, titers in pigs were lower and, in some contact pigs, were below the positive threshold. These findings are comparable with outcomes reported for pH1N1 virus infection of pigs and ferrets (36,37,39,40) and a comparison of swine H1 viruses, including H1N2v strains, when infecting ferrets (41). A North American reassortant H1N1 swine IAV incorporating pH1N1-origin polymerase acidic, NP, and M genes also reportedly showed similar replication kinetics to a swine IAV pH1N1 isolate when infecting ferrets (14).…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies examining the pathogenesis of variant IAV have shown these viruses to be well adapted to replication in the respiratory tissue of ferrets (24,45,46). Virus titers and kinetics of virus detection in the nasal swabs from ferrets infected with sw/OH/2017 were similar to previously reported data with H1N1v, H1N2v, and H3N2v.…”
Section: Figsupporting
confidence: 83%
“…Analysis of variant influenza viruses has shown H1N1v and H3N2v to be identical to IAV isolated from pigs at the same fair, suggesting that a subpopulation of swine lineage IAV are capable of replication in humans in situations of high viral titers and close contact (19,20,22,44). Previous risk assessment studies focused on direct inoculation of ferrets with variant IAV isolated from humans (23,24,45,46). In this study, we sought to recapitulate the primary step of interspecies transmission by modeling the swine-human transmission potential using a ferret surrogate.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate the pathogenicity of the two H1N1 viruses in mammalian species, we inoculated BALB/c mice with 10 6 EID 50 /50µL of each virus and determined virus replication, mortality, and pathology. Previous studies showed that the H1N1 virus and its variant viruses isolated from different hosts and cases displayed a different pathogenicity in mice [39][40][41][42][43][44][45]. Those isolates showed effective replication in lungs but varied in their ability to cause morbidity.…”
Section: Discussionmentioning
confidence: 99%